Suck it up - Una Krizmanić Ožegović; Stanislava Nikolić Aras ([sic])
“C'mon, let's go people, it's the coppers,” she would shout sometimes, out of the blue, but for the most part, Gracijela was saying things to herself on a loop and dragging her feet in shabby men's shoes. The day was cut off by a sharp siren – an air raid. On that note, all the doors opened. People came out of lunch-infused kitchens and headed towards our street. With her hair combed, Mrs. Doma straightened her skirt and calmly locked her green wooden door. Jelka limped fast from her street, so they met at the corner and walked together. Old men, Schmatte and Owl, both awarded the People's Liberation Movement medals for serving in the Second World War, tapped their canes across their rain-soaked courtyards. The 48 Prosciutto walked slowly with hands behind his back and seemingly indifferent, just going out for a walk, no intention of hiding from the planes. He was just passing through the street and saying hi to the neighbors: “You good, Mrs. Jele?”“All right, all right, Mr. Schmatte.”